2008
DOI: 10.1007/s00204-008-0334-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the GSTT1 activity by the GSTM1 phenotype in a sample of Italian farm-workers

Abstract: Glutathione S-transferase (GST) isozymes catalyze nucleophilic attack by reduced Glutathione (GSH) on a variety of electrophilic compounds and play a central role in biotransformation of xenobiotics (Hayes et al., Annu Rev Pharmacol Toxicol 45:51-88, 2005). We performed a case-control study to evaluate the GSTM1 and GSTT1 polymorphisms and to investigate if exposure to pesticides conditions the GSTT1 activity level in 115 healthy controls and 90 farm-workers exposed to pesticides. Polymorphisms were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Furthermore, a significant interaction between the GSTM1 positive genotype and other GST variants has been highlighted in the genotoxic effect analysis of tobacco smoke (31). The inducibility of the GST system may explain the interactions between GST enzymes (32). The GSTA1*-69C/T variant causes a deficiency expression in the GSTA1 enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a significant interaction between the GSTM1 positive genotype and other GST variants has been highlighted in the genotoxic effect analysis of tobacco smoke (31). The inducibility of the GST system may explain the interactions between GST enzymes (32). The GSTA1*-69C/T variant causes a deficiency expression in the GSTA1 enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…Compensatory up-regulation of other genes may occur in the absence of functional GSTM1 and GSTT1 enzymes. The GSTM1*0/*0 genotype has been associated with a significant increase in GSTT1 activity after xenobiotic exposure among Italian farm workers [14]. The authors conclude that the finding suggests a regulative mechanism common to the two enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…One study found the GSTM1*0/*0 genotype to be associated with a significant increase in GSTT1 activity after exposure to xenobiotics. Subjects with the GSTM1*0/*0/GSTT1*1 genotype had higher enzyme activity than subjects with GSTM1*1/ GSTT1*1 indicating potential overcompensation [14]. Whether overcompensation also takes place during OC exposure in women lacking one of the GSTM1 or GSTT1 genes is currently unknown.…”
Section: Introductionmentioning
confidence: 97%
“…However the loss of GSTT1 enzyme activity by deletion polymorphism can affect other metabolic pathways that could be strongly activated, for example other genes in the GST family, thus causing the pre-ventive effect on osteoblast cells. This fact could be supported, however indirectly, by the study of Fuciarelli et al [32] who hypothesized that there is probably a regulative compensatory mechanism that involves the increased activity of GSTT1 enzyme when the GSTM1 enzyme is lacking. Further studies are needed on the activities of GSTT1 and GSTM1 and their relation to deletion genotypes.…”
Section: Discussionmentioning
confidence: 99%